Materiais de eficiência melhorada baseados em zeólita clinoptilolita, macro e micronutrientes e biopolímeros - Binotto, Vilma Damian Dias Neves (Universidade Federal de São Carlos, 2021)
There has been exponential population growth and, consequently, an intensification in the use of fertilizers. The overuse of fertilizers generates environmental impacts, due to the leaching and volatilization of fertilizers, which can contaminate soil and water. One of the ways to minimize these impacts is to use enhanced efficiency fertilizers which allows the proper use of nutrients according to the demand of the plants, reducing both the environmental and economic impact. Additionally, the use of materials from natural sources and with potential for biodegradation contributes to the sustainability of system. In this work, tablets of enhanced efficiency were developed, composed of clinoptilolite zeolite matrix adsorbed with macro (K) and micronutrients (Cu, Zn, Mn, Fe) and covered by crosslinked alginate and chitosan. Initially, the process of adsorption of nutrients by zeolite was evaluated and applied to mathematical models to determine the kinetics and isotherm of adsorption. From the zeolite / nutrient powder, tablets were obtained by pressing and covered with polymers using dipping technique. Through the kinetics process, it was possible to conclude that K fits the first-order equation, that is, it is adsorbed on the zeolite by physisorption. The micronutrients are adsorbed to the zeolite by chemisorption. Through the difference between the adsorption capacity of the nutrients and the concentration, it was determined that the Langmuir’s isotherm was most suitable for the nutrient ions evaluated implying that the nutrients are linked by monolayer. The Freundlich isotherm, in which nutrients tend to organize themselves in multilayers under the zeolite, was the one most suitable for Fe. Preliminary data on the release of tablets in water show that the coating prolongs the release of nutrients. Within this context, it was found that this theme is very promising to be worked on in the classroom, as there are a variety of themes (contamination of effluents, water, fertilizers, food, plant growth, etc.) that can be worked in an interdisciplinary way, with this, two learning proposals were developed addressing these topics. We can conclude that the work has the potential to contribute to a better use of nutrients by plants and the reduction of environmental impacts, in addition to promoting an important approach on sustainability for teaching
Efficiency-enhanced materials based on clinoptilolite zeolite, macro and micronutrients and biopolymers
Keywords: Alginato reticulado; Fertilizante de eficiência melhorada; Macro e micronutrientes; Pastilhas; Quitosana; Zeólita; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA INORGANICA::NAO-METAIS E SEUS COMPOSTOS